Digitalisasi Pelayanan Publik di Indonesia: Dampak Ekonomi, Efisiensi Anggaran, dan Inovasi Tata Kelola Pemerintahan - Novia Angelita Margaretha Silitonga (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
This study aims to analyze the impact of digitalization of public services on budget efficiency, governance innovation, and economic growth in Indonesia. Using qualitative methods through a literature review approach, this study explores various academic sources and policies related to the digital transformation of government. The results show that the implementation of the Electronic-Based Government System (SPBE), e-budgeting, and online public services have a positive impact on increasing transparency, accelerating service delivery, and reducing operational costs. Furthermore, digitalization has contributed to the creation of a new economic ecosystem, which in turn strengthens the principles of good governance in government. However, several obstacles remain to be overcome, such as infrastructure inequality, low digital literacy among the public, and weak regulations supporting the application of technology in public services. Therefore, the success of digitalization of public services depends heavily on the readiness of human resources, the strengthening of more inclusive policies, and synergy between government agencies so that digital transformation can be effective, sustainable, and reach all levels of society.